Legal Analysis of Criminal Sanctions Against Recidivist Children in the Perspective of the Juvenile Criminal Justice System - Marwan Suliandi; Tuti Widyaningrum (LEGAL BRIEF, 2026)
This study attempts to investigate how criminal penalties are applied to kids who commit repeat offenses (recidivism) and how well they operate in the context of child protection. The primary issue is the conflict between the state's duty to give restorative justice principles top priority and using criminal penalties to have a deterrence impact. Normative juridical research using a statutory approach is the methodology employed. According to the study's findings, repeat offenders typically face harsher penalties than first-time offenders, although they are still constrained by the best interests of the kid premise.